Genetic analysis in ridge gourd [Luffa acutangula (Roxb.) L.] under hot arid conditions (Indian Journal of Arid Horticulture, 2025)
The present investigation was conducted to determine variability, heritability, genetic advance and correlation of different yield and yield contributing characters of ridge gourd. The range of variation was higher in fruit length (3.66- 26.93cm). The highest GCV (29.40) and PCV (32.29) was recorded in node at which first female flower appeared. The heritability estimate values in broad sense were higher for all the traits except number of branches/ plant, days to first female flower and days to first fruit harvest. The marketable fruit yield per plant had positive and significant correlation with fruit weight (0.786) and fruit length (0.448) at phenotypic level.
Keywords: Ridge gourd; variability; GCV; PCV; heritability; genetic advance